2017
DOI: 10.1002/mana.201600529
|View full text |Cite
|
Sign up to set email alerts
|

Chow ring of generic flag varieties

Abstract: Let G be a split semisimple algebraic group over a field k and let X be the flag variety (i.e., the variety of Borel subgroups) of G twisted by a generic G‐torsor. We start a systematic study of the conjecture, raised in in form of a question, that the canonical epimorphism of the Chow ring of X onto the associated graded ring of the topological filtration on the Grothendieck ring of X is an isomorphism. Since the topological filtration in this case is known to coincide with the computable gamma filtration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…For the variety of Borel subgroups X = E/B, twisted by E (i.e., E/B is a twisted form of G/B, where B ⊂ G is a Borel subgroup), Karpenko conjectured that the morphism φ is an isomorphism in [4], where he confirmed the conjecture for a simple group G of type A or C. Indeed, by [4,Lemma 4.2] this conjecture is equivalent to the same statement, after replacing the Borel subgroup B by a special parabolic subgroup P of G (i.e., any P -torsor over any field extension of k is trivial). Moreover, in [3,Theorem 1.2] he showed that the conjecture holds for a wider class of groups G including special orthogonal groups and the exceptional groups of types G 2 , F 4 , and simply connected E 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For the variety of Borel subgroups X = E/B, twisted by E (i.e., E/B is a twisted form of G/B, where B ⊂ G is a Borel subgroup), Karpenko conjectured that the morphism φ is an isomorphism in [4], where he confirmed the conjecture for a simple group G of type A or C. Indeed, by [4,Lemma 4.2] this conjecture is equivalent to the same statement, after replacing the Borel subgroup B by a special parabolic subgroup P of G (i.e., any P -torsor over any field extension of k is trivial). Moreover, in [3,Theorem 1.2] he showed that the conjecture holds for a wider class of groups G including special orthogonal groups and the exceptional groups of types G 2 , F 4 , and simply connected E 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Let B be a Borel subgroup of G. There is a conjecture (see [, Conjecture 1.1]) that for the variety X:=E/B – a generic variety of complete flags — the canonical epimorphism of the Chow ring CH X onto the associated graded ring GK(X) of the topological filtration on the Grothendieck ring K(X) is an isomorphism. Since the ring K(X) is computed and the topological filtration on it is known to coincide with the computable gamma filtration [, Example 2.4], this conjecture, proved in several cases already, provides a way to compute the Chow ring.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover we take G a versal G k -torsor i.e., G is isomorphic to G k(S) -torsor over Spec(k(S)) given by the generic fiber of GL N → S where S = GL N /G k for an embedding G ⊂ GL N ( for the properties of a versal G k -torsor, see §3 below or see [Ga-Me-Se], [To2], [Me-Ne-Za], [Ka1]). When G/B k = F is a versal flag variety, it is known ([Me-Ne-Za], [Ka1]) that CH * (F) is generated by Chern classes. Hence we know gr * γ (F) ∼ = gr * geo (F).…”
Section: Introductionmentioning
confidence: 99%
“…Hence we know gr * γ (F) ∼ = gr * geo (F). Karpenko conjectures that the above I(1) = 0 ( [Ka1], [Ka2]). In this paper, we try to compute gr * γ (G/T ) for G = Spin(2ℓ + 1).…”
Section: Introductionmentioning
confidence: 99%